Increased carotid artery intima-media thickness may be associated with stroke in primary antiphospholipid syndrome. Issue 7 (1st July 2003) - Medina, G; Casaos, D; Jara, L J; Vera-Lastra, O; Fuentes, M; Barile, L; Salas, M
Abstract : Objective: To investigate the prevalence and clinical significance of carotid artery intima-media thickness (IMT) in patients with primary antiphospholipid syndrome (APS). Methods: 28 patients with primary APS with at least a five year follow up, and 28 healthy subjects, matched by age and sex, were included in the study. Colour Doppler with high resolution B mode carotid ultrasonography and spectral analysis were performed in patients and controls. Information on cardiovascular risk factors and the clinical course were collected. Results: The mean (SD) age of patients and controls (12 male, 16 female in each group) was 40 (8.5) years; the mean (SD) disease duration 7.7 (3) years. Carotid artery IMT was found in 23/28 patients (2.6 (1.14) mm) and 7/28 controls (1.2 (0.44)) (p=0.0001). A decrease in the lumen diameter was also found in 11/28 patients with primary APS without carotid atherosclerotic plaque, and 2/28 controls (p=0.004). Hyperlipidaemia, diabetes, smoking, obesity, and hypertension were not associated with carotid artery IMT. Patients with carotid artery IMT had arterial vascular disease more often than patients without: 9/23 v 0/5 (p<0.009). These patients had stroke (seven patients), myocardial infarction (one), and mesenteric thrombosis (one). Subjects with IMT had a threefold higher risk for stroke than those without IMT (95% CI 0.78 to 14.3). Conclusions: Patients with primary APS have a high prevalence of carotid artery IMT and a decreased lumen diameter. IMT in primary APS may be associated with stroke. Patients with primary APS with IMT must be considered as carriers of atherosclerosis.